Imaging of Injectable Hydrogels Delivered into Myocardium with SPECT/CT. Issue 14 (15th June 2020) - Uman, Selen; Wang, Leo L.; Thorn, Stephanie L.; Liu, Zhao; Duncan, James S; Sinusas, Albert J.; Burdick, Jason A.
Abstract: Injectable hydrogels are being widely explored for treatment after myocardial infarction (MI) through mechanical bulking or the delivery of therapeutics. Despite this interest, there have been few approaches to image hydrogels upon injection to identify their location, volume, and pattern of delivery, features that are important to understand toward clinical translation. Using a hyaluronic acid (HA) hydrogel as an example, the aim of this study is to introduce radiopacity to hydrogels by encapsulating a clinically used contrast agent (Omnipaque Iohexol, GE Healthcare) for imaging upon placement in the myocardium. Specifically, iohexol is encapsulated into shear‐thinning and self‐healing hydrogels formed through the mixing of HA‐hydrazide and HA‐aldehyde. Upon examination of a range of iohexol concentrations, a concentration of 100 mg mL −1 iohexol is deemed optimal based on the greatest contrast, while maintaining hydrogel mechanical properties and acceptable injection forces. In an acute porcine model of MI, hybrid single‐photon emission computed tomography/computed tomography (SPECT/CT) perfusion imaging is performed immediately and 3–4 days after hydrogel delivery to assess radiopacity and verify the hydrogel location within the perfusion defect. Hybrid SPECT/CT imaging demonstrates excellent radiopacity of the hydrogel within the perfusion defect immediately after intramyocardial hydrogel injection, demonstrating the feasibility of this method for short‐term noninvasive hydrogel monitoring. Abstract : Injectable hydrogels are being developed for treatment of myocardial infarction. To better understand hydrogels after injection to the myocardium, radiopacity is introduced through encapsulation of the contrast agent iohexol. The incorporation of iohexol does not change hydrogel properties, but allows for imaging upon injection. The signal is lost within days, so it is most useful for understanding the initial hydrogel placement.